The evaluation of risky interrelated investments - Hillier, Frederick S. (Amsterdam : North-Holland Pub. Co., 1969)
This book has explored the problem of evaluating a single risky investment or a set of independent risky investments. It attempt to initiate explorations on developing systematic procedures for evaluating a set of large, risky, interrelated investments.
Includes index
Bibliography: p. 101-110.
usc 21/05/18
Loans
Keywords: Capital investments; Risk